Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper on Indonesia explains through econometric analysis the contribution of different factors to export growth and assesses the prospects for its maintenance in the future. The paper reviews developments in Indonesian export growth since 1970. It develops a model of export demand and export supply, provides empirical estimates from the model, and the implications of the results. The paper also addresses medium-term prospects for export growth on the basis of the estimated model and the possible impact of exchange rate changes.